Internet connectivity disruption in Guatemala (Guatemala) - Voidly (2026)
CRITICAL severity disruption detected in Guatemala. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: GT-2026-0012
Keywords: internet disruption; GT; disruption; critical